Application for an Engineering Design Education of Lunar/Planetary Exploration - HARUYAMA, Junichi; MIURA, Sei-ichiro; KITAMURA, Kentarou (TRANSACTIONS OF THE JAPAN SOCIETY FOR AERONAUTICAL AND SPACE SCIENCES, AEROSPACE TECHNOLOGY JAPAN, 2016)
In context of the Engineering Design Education, actual lunar exploration mission “Unprecedented Zipangu Underworld of the Moon Exploration (UZUME) project” has strong potential to be applied to Project Based Learning (PBL) program in the Engineering Design Education. In this paper, we introduce student's experience for a conceptual design of lunar exploration mission and discuss its educational effectiveness. Through participation to the Satellite Design Contest, it is confirmed that students can acquire integrated ability of engineering subjects and that process of proposal is quite consistent with concept of the Engineering Design Education. In particular, merging of many engineering subjects and long-term group work are quite effective to cultivate student's engineering design abilities.